THE PROCESS OF AGING AND THE ELDERLY UNDER THE VISION OF UNIVERSITY STUDENTS IN THE HEALTH FIELD - Chaves, Gisele Ferreira; Calvim, Eliziane Nitz de Carvalho; Ferraz, Renato Ribeiro Nogueira; Oliveira, Rafaela Sanches de (Saúde (Santa Maria), 2015)
Objective: Verify the perspective of university students of health facing the process of aging and about the elderly and the adoption of healthy habits, that may help to prevent and/or control illnesses and maintain the functional capacity of the aging. Methods: A descriptive cross-sectional study composed of 200 college students. Questionnaires were applied to students at Universidade Nove de Julho (UNINOVE), Sao Paulo, Brazil,in the physical therapy, nursing and psychology programs. Of the 200 questionnaires, 13 were excluded because they were incomplete. Results: 85.00% of respondents believe that successful aging is aging with good physical and mental condition, 47.60% fear being dependent on others, 28.50% believe that they become elderly when they present difficulties in performing everyday tasks and 70.40% always respect the rights of the elderly. Overall, respondents do not maintain healthy life habits that would lead to a successful process of aging, 65.2% do not exercise. Conclusion: The results showed that in most cases the interviewees respect the rights of the elderly; however, they have a negative view of the aging process and the elderly. Descriptors: Aging; Education; Health of the Elderly